Penerapan Kurikulum Merdeka pada Mata Pelajaran PAI di SMA Negeri 1 Candipuro - Awaludin, Robi; Dewi, Gustianti (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2024)
The aim of this research is to find out how the Merdeka Curriculum is implemented in Islamic Religious Education subjects at SMA Negeri 1 Candipuro Lampung Selatan, starting from how to implement the Merdeka Curriculum which consists of teacher preparation, how to implement it and how to assess it, then what problems occur. and what efforts educators have made in implementing the Independent Curriculum in Religious Education subjects. This research uses research methods with the type of field research and the nature of descriptive qualitative research. Data collection methods are through observation, interviews and documentation. Primary data was obtained through interviews and observation while secondary data was obtained through documentation. The results of this research can be concluded that the implementation of the Merdeka curriculum in the Islamic Religious Education learning subject consists of 3 activities, first there are preliminary activities, then core activities and closed with closing activities, plus the P5 project. Then there are problems that occur in the implementation of Islamic Religious Education learning, namely educators lacking training, less than optimal differentiated learning and mindset. So the efforts made to overcome these problems are by attending internal/external workshops, increasing creativity as a teacher and sharing with fellow educators or with people who know more (often ask questions).